2001
DOI: 10.1007/s001090100198
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of leptin production: sympathetic nervous system interactions

Abstract: Leptin is secreted primarily from white adipose tissue and stimulates long-form OB-Rb receptors in the hypothalamus to decrease food intake and increase energy expenditure. A variety of neuropeptides are involved in these responses, including neuropeptide Y, agouti-related protein, the prepro-melanocortin system and cocaine- and amphetamine-regulated transcript. OB-Rb receptors (and other receptor isoforms) are also found in peripheral tissues. Leptin is now known to have a wide range of peripheral actions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
168
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(188 citation statements)
references
References 179 publications
8
168
0
12
Order By: Relevance
“…The reduced caloric efficiency in morphine-treated rats was probably a consequence of increased sympathetic neuronal outflow (Akana et al, 1999). Reduced plasma insulin and leptin concentrations also suggest increased sympathetic activity in morphine-treated rats (Bartness, 1998;Rayner and Trayhurn, 2001). In support of this, previous studies have shown that opioid dependence and withdrawal are associated with increased noradrenergic and catecholaminergic activity in brain and hypothalamus (Ahtee et al, 1989;Fuertes et al, 2000;Milanes et al, 1993Milanes et al, , 1997Milanes et al, , 1998.…”
Section: Energy Balancementioning
confidence: 63%
“…The reduced caloric efficiency in morphine-treated rats was probably a consequence of increased sympathetic neuronal outflow (Akana et al, 1999). Reduced plasma insulin and leptin concentrations also suggest increased sympathetic activity in morphine-treated rats (Bartness, 1998;Rayner and Trayhurn, 2001). In support of this, previous studies have shown that opioid dependence and withdrawal are associated with increased noradrenergic and catecholaminergic activity in brain and hypothalamus (Ahtee et al, 1989;Fuertes et al, 2000;Milanes et al, 1993Milanes et al, , 1997Milanes et al, , 1998.…”
Section: Energy Balancementioning
confidence: 63%
“…It is, however, noteworthy to note that leptin gene expression in adipocytes and circulating leptin concentrations are subject to short-term regulation, especially by nutritional status [12][13][14]. For example, food deprivation decreases plasma leptin concentrations with decreased mRNA transcription in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The WAT is innervated by the sympathetic nervous system (SNS), although less extensively than brown adipose tissue (BAT) (Bartness et al, 2001). The SNS is considered to be the major physiological regulator of lipolysis in WAT and has been implicated in the regulation of cell number and the synthesis of several adipokines, particularly leptin (Rayner and Trayhurn, 2001). In a number of murine tissues, the development and survival of sympathetic neurons depend upon the presence of target-derived neurotrophins the best characterized of which is nerve growth factor (NGF) in BAT (Nisoli et al, 1996) and WAT (Peeraully et al, 2004).…”
mentioning
confidence: 99%